Memperkuat Loyalitas Melalui Kepercayaan, Kepuasan Dan Komitmen Studi Pada Nasabah PT. Bank Cimb Niaga - Sri Widyastuti (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2015)
Customer loyalty is ‘suspected’not been able to optimizationrepetition of transactions, customer recommendation and durability with the establishment relationship quality of the trust, customer satisfaction and commitment. Therefore, research conducted on Bank CIMB Niaga aims to determine the extent of the trust, and commitment to customer satisfaction can increase X-tra and TabunganKU savings customer loyalty. This research is verification and the method of research is explanatory survey method, the sample is 160 customer X-tra and tabunganKU savings in the branch office Bank CIMB Niaga Bintaro. The analytical method used is structural equation model. The results showed loyalty can be achieved with relationship quality for customers through the establishment of trust, and commitment to customer satisfaction, which all three have a positive influence. Therefore, the management of Bank CIMB Niaga need to improve their ability in trust, satisfactionand commitmentwith the bank's customers to become increasingly favored customers.